The Art of Tokenization: Blockchain Affordances and the Invention of Future Milieus - Laura Lotti (Media Theory)
Ten years after the introduction of the Bitcoin protocol, an increasing number of art-tech startups and more or less independent initiatives have begun to explore second-generation blockchains such as Ethereum and the emergent practice of tokenization (i.e., the issuance of new cryptoassets primarily to self-fund decentralized projects) as a means to intervene in the structures and processes underlying the rampant financialization of art. Yet amidst the volatility of the cryptocurrency market, tokenization has been critiqued as a way to reinscribe and proliferate current financial logics in this new space. Acknowledging such critiques, in this essay I foreground the novelty of cryptotokens and blockchains by exploring different examples of how tokenization has been deployed in the art market-milieu. In spite of recent attempts to extend the scarcity-based paradigm to blockchains, I argue that cryptotokens do introduce differences in kind in the ways in which value generation and distribution are expressed and accounted for in digital environments. In this context, artistic approaches to tokenization can illuminate new aspects of the affordances of these technologies, toward the disintermediation of art production and its networked value from the current institutional-financial milieu. This can open up new ways to reimagine and reprogram financial and social relations, and gesture toward new opportunities and challenges for a practice of digital design focused on the ideation and realization of cryptoeconomic systems.